Relationship between cultural food taboos and maternal and child nutrition: A systematic literature review - Dembedza, Vimbainashe Prisca; Mapara, Jacob; Chopera, Prosper; Macheka, Lesley (The North African Journal of Food and Nutrition Research, 2025)
Background: The escalating frequency and severity of climate extremes, such as floods and droughts, are projected to exacerbate the burden of malnutrition. This issue is particularly pronounced among vulnerable populations, including children under five years of age and pregnant women, wherein malnutrition may be further aggravated by the prevalence of culturally ingrained food taboos. While food taboos are often instituted with the intent of safeguarding the health of specific demographic groups, they may also restrict the impose restrictions on the consumption of essential nutrients, thereby impeding optimal growth and development. Aims: This study aimed to explore the relationship between culturally ingrained food taboos and the nutritional status of mothers and children. Methods: A systematic literature review was conducted across a range of electronic databases, including Web of Science, PubMed, Google Scholar, and Semantic Scholar. Following the removal of duplicate entries and the application of pre-defined inclusion criteria, a total of 45 articles were selected for comprehensive analysis. The methodological rigor of the included studies was appraised using the AMSTAR checklist. Results: The earliest article identified within this review was published in 1994. The majority of the studies were conducted in African countries (24), followed by Asia nations (15). Food taboos predominantly involved plant-based sources (13 articles), with animal-based food sources also frequently subject to prohibitions. Of the reviewed articles, 62.2% focused on women of childbearing age, while six articles specifically addressed children. Notably, only two studies incorporated anthropometric measurements to establish a direct association between food taboos and nutritional outcomes. Conclusion: Although scholarly inquiry into the intersection of food taboos and maternal and child nutrition has witnessed expansion in recent years, there remains a critical need for more exhaustive studies that employ anthropometric measurements to elucidate the impact of food taboos on nutritional status. Such research would yield more definitive insights into the effects of food taboos on nutritional well-being and inform the development of targeted interventions to address this issue. Keywords: Culture, Taboos, Women, Child nutrition, Malnutrition.